Syndrome Differentiation and Treatment Regularity in Traditional Chinese Medicine for Type 2 Diabetes: A Text Mining Analysis - Dou, Zhili; Xia, Ye; Zhang, Jiawei; Li, Yizhen; Zhang, Yunan; Zhao, Lei; Huang, Zhe; Sun, Haonan; Wu, Lin; Han, Dongran; Liu, Yixing (Frontiers in Endocrinology, 2021)
Objective: The goal of this study was to systematically summarize and categorize the syndrome differentiation, medication rules, and acupoint therapy in the domestic traditional Chinese medicine (TCM) literature on Type 2 diabetes mellitus (T2DM), such that guidelines and new insights can be provided for future practitioners and researchers. Methods: Taking randomized controlled trials (RCTs) on the treatment of T2DM in TCM as the research theme, we searched for full-text literature in three major clinical databases, including CNKI, Wan Fang, and VIP, published between 1990 and 2020. We then conducted frequency statistics, cluster analysis, association rules extraction, and topic modeling based on a corpus of medical academic words extracted from 3,654 research articles. Results: The TCM syndrome types, subjective symptoms, objective indicators, Chinese herbal medicine, acupuncture points, and TCM prescriptions for T2DM were compiled based on invigorating the kidney and Qi, nourishing Yin, and strengthening the spleen. Most TCM syndrome differentiation for T2DM was identified as “Zhongxiao” (the lesion in the spleen and stomach) and “Xiaxiao” (the lesion in the kidney) deficiency syndromes, and most medications and acupoint therapies were focused on the “Spleen Channel” and “Kidney Channel.” However, stagnation of liver Qi was mentioned less when compared with other syndromes, which did not have symptomatic medicines. Conclusion: This study provides an in-depth perspective for the TCM syndrome differentiation, medication rules, and acupoint therapy for T2DM and provides practitioners and researchers with valuable information about the current status and frontier trends of TCM research on T2DM in terms of both diagnosis and treatment.